2019
DOI: 10.3389/fgene.2019.00195
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of IQ, Phonemic Decoding Skill, and Academic Achievement

Abstract: The aim of this study was to examine whether phonemic decoding skill (deficits of which characterize dyslexia) shares genetic and/or environmental covariance with scholastic abilities independent of general intelligence. Non-word reading ability, verbal and non-verbal IQ, and standardized academic achievement (Queensland Core Skills Test; QCST) were measured in Australian twins (up to 876 twin pairs and 80 singleton twins). Multivariate genetic analysis showed the presence of a general genetic factor, likely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Recent results in the area of genetics provide support for this. For example, a general genetic factor has been suggested that would explain variation in both non-verbal intelligence and reading ( Lazaroo et al, 2019 ), and significant overlap between word reading and intelligence has emerged in a recent genome-wide association study ( Price et al, 2020 ). Further, it has been shown for dyslexia that there is an interrelation between genotype, brain anatomy, and neurofunctionality ( Skeide et al, 2015 , 2016 ; Neef et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent results in the area of genetics provide support for this. For example, a general genetic factor has been suggested that would explain variation in both non-verbal intelligence and reading ( Lazaroo et al, 2019 ), and significant overlap between word reading and intelligence has emerged in a recent genome-wide association study ( Price et al, 2020 ). Further, it has been shown for dyslexia that there is an interrelation between genotype, brain anatomy, and neurofunctionality ( Skeide et al, 2015 , 2016 ; Neef et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%